Modernization of Islamic Education in Indonesia Karel A Steenbrink's Perspective Systematic Literature Review - Euis Asyiah; Bayu Pramono; Supianto; Enung Nugraha (South Sulawesi Education Development (SSED), 2025)
This research aims to review the Modernization of Islamic Education in Indonesia, the challenges, and how the modernization of Islamic Education develops. The method used in this study is a literature review, the data of which was obtained by reviewing several database sites, namely Google Scholar. The study results show that traditional educational institutions such as Islamic boarding schools that initially only taught religious knowledge have opened themselves up by carrying out general education for students. However, the dualism of the Ministry of Religion and the Ministry of Education is a problem that must be solved. The researcher argues that these two institutions must synergize well and have synchronization in terms of education policies. Kiyai, who became a teacher in the traditional era, now has to collaborate with modern teachers to build a modern Islamic education civilization. The existence of kiyai and teachers is not to be separated but must be synergized to create better competencies (knowledge, skills, and attitude) in the young generation of Islam.